Diseño de una red de distribución logística para el Grupo Cosalco (2021)
This document presents as its main objective the design of a distribution network for the Cosalco Group, initially a diagnosis was made of both the external and internal environment in order to find influential external factors in the development of operations and understand the logistics distribution process that operates the organization under study respectively, after this those factors to be taken into account in the design of a logistics distribution network where it is identified structural and associated cost elements; subsequently established a design proposal for the current configuration, is based on the conceptualization of five distribution models, a mapping of correspondence through checklists and validation through primary sources, then a mathematical model was developed to determine the optimal amounts of product availability, finally a financial study was carried out to determine the economic viability of the proposed design alternative.